Stiletto - Robbins, Harold, 1916-1997 (London New English Library, 1978)
Cesare Cardinali is a young Italian aristocrat with an inborn penchant for violence who owes his lush lifestyle to the favors of a Mafia overlord. He is more than happy to return the favors by silencing four men awaiting trial in a sensational case against organized crime. Special Agent George Baker is the man who has assembled the evidence to put those same four men away for life. When one is knifed under the watchful eye of a policeman outside a New York courtroom, and another is found slumped over a Las Vegas gaming table, Baker enters a cat-and-mouse game to entrap Cardinali before his whole case is destroyed.
Keywords: Mafia -- Government investigators -- Assassins -- United States. Federal Bureau of Investigation -- United States